Association between short-term exposure to ambient fine particulate matter and myocardial injury in the CATHGEN cohort. (15th April 2021) - Zhang, Siqi; Breitner, Susanne; Cascio, Wayne E.; Devlin, Robert B.; Neas, Lucas M.; Ward-Caviness, Cavin; Diaz-Sanchez, David; Kraus, William E.; Hauser, Elizabeth R.; Schwartz, Joel; Peters, Annette; Schneider, Alexandra
Abstract: Exposure to fine particulate matter (PM2.5 ) has been associated with a higher risk for coronary events. Elevated circulating cardiac troponins (cTn) are suggestive of myocardial injury in both ischemic and non-ischemic conditions. However, little is known about the association between PM2.5 and cTn. In this study, we investigated short-term PM2.5 effects on cardiac troponin T (cTnT), as well as N-terminal-pro brain natriuretic peptide (NT-pro BNP) and inflammatory biomarkers among cardiac catheterized participants. We analyzed 7444 plasma cTnT measurements in 2732 participants who presented to Duke University Hospital with myocardial infarction symptoms between 2001 and 2012, partly along with measurements of NT-pro BNP and inflammatory biomarkers. Daily PM2.5 concentrations were predicted by a neural network-based hybrid model and were assigned to participants' residential addresses. We applied generalized estimating equations to assess associations of PM2.5 with biomarker levels and the risk of a positive cTnT test (cTnT > 0.1 ng/mL). The median plasma cTnT concentration at presentation was 0.05 ng/mL and the prevalence of a positive cTnT test was 35.4%. For an interquartile range (7.6 μg/m 3 ) increase in PM2.5 on the previous day, cTnT concentrations increased by 7.7% (95% CI: 3.4–12.3) and the odds ratio of a positive cTnT test was 1.08 (1.01–1.16). Participants under 60 years (effect estimate: 15.2%; 95% CI: 7.4–23.5) or living in rural areas (12.3%; 95% CI: 4.8–20.3) were more susceptible. There was evidence for increases in fibrinogen and NT-pro BNP associated with elevated PM2.5 on the concurrent and previous two days. Our study suggests that acute PM2.5 exposure may elevate indicators of myocardial tissue damage. This finding substantiates the association of air pollution exposure with adverse cardiovascular events. Graphical abstract: Image 1 Highlights: Cardiac troponin T was measured in both cardiac ischemic and non-ischemic conditions. Acute PM2.5 exposure was associated with increased plasma cardiac troponin T (cTnT). PM2.5 effects on cTnT were stronger in people under 60 years or living in rural areas. Acute PM2.5 exposure was associated with increased fibrinogen and NT-pro BNP. Evidence of PM2.5 -related myocardial injury that could occur without acute MI.